Detection of intrinsic cholinergic system in the human lacrimal drainage system: evidence and potential implications - Mohammad, Javed Ali; Glöckner, Mareile; Schicht, Martin; Bräuer, Lars; Paulsen, Friedrich (Graefes Archive For Clinical and Experimental Ophthalmology, 2018)
PURPOSE: To investigate the presence and distribution of epithelial and non-epithelial cholinergic system and cholinergic brush cells in the human lacrimal drainage system. METHODS: The study was performed on fresh frozen human cadaveric samples of the lacrimal drainage system. Immunohistochemistry was performed for assessing the presence and distribution of cholinergic brush cell proteins-villin, acetylcholine synthesizing enzyme, choline acetyltransferase (ChAT); vesicular acetylcholine transporter (VAChT); components of canonical taste transduction signaling cascade, phospholipase C β2 (PLCβ2), and transient receptor potential cation channel, subfamily M, and member 5 (TRPM5). In addition, immunoreactivity to carbonic anhydrase 4 (CA4) was assessed. The immunoreactivity was scored as positive or negative and the distribution patterns in the canaliculi, lacrimal sac, and nasolacrimal duct were investigated. In addition, ultrastructural analysis was performed to ascertain the presence of brush cells by means of scanning electron microscopy (SEM). RESULTS: Villin revealed immunoreactivity in the superficial epithelial cells of lacrimal sac and nasolacrimal ducts. Positive immunoreactivity was also found for ChAT, VAChT, TRPM5, and PLCβ2. ChAT expression was limited to the superficial epithelial layers of the lacrimal sac epithelium. TRPM5 and PLCβ2 were expressed on the cell membranes, cytoplasm, and basolateral surfaces of the lacrimal sac epithelium and also showed strong expression in the submucosal glandular acinar cells. VAChT showed strong expression in the canaliculus and lacrimal sac and was expressed on the surface of the superficial epithelial cells and the submucosal glandular acinar cells and lining of the blood vessels. There was a uniformly negative immunoreactivity for CA4. SEM revealed single epithelial cells with dense tuft of rigid apical microvilli in the lacrimal sac and nasolacrimal ducts. CONCLUSIONS: This study provides a proof of principle for the presence of an intrinsic epithelial cholinergic mechanism in the lacrimal drainage system.
EVALuna2:35303